How Efficient are Intercity Railway Prices and Frequencies in Europe? Comparing a Corridor in Belgium and in France. (1st October 2019) - Monchambert, Guillaume; Proost, Stef
This paper studies the efficient pricing of medium-distance passenger rail in Europe. Current fares and frequencies are compared with three alternatives: first-best where road congestion is internalised; second-best where no road tolls are implemented; and third-best where a maximum rail deficit is also imposed. We find that second-best fares depend strongly on the non-internalised road congestion and on the price elasticity of the passengers, complicating the derivation of a national or regional fare structure. Second-best achieves a significant share of the first-best benefits, but adding a budget constraint makes second-best solutions difficult to implement for some corridors.